2020
DOI: 10.5771/2365-1083-2020-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Verbreitung und Einflussfaktoren von Homophobie unter Jugendlichen und Erwachsenen. Befragungsbefunde aus der Schweiz und Deutschland

Abstract: Homophobie, d. h. die Abwertung von nicht-heterosexuellen Menschen, ist sowohl in der Schweiz als auch in Deutschland existent. Im Beitrag wird einerseits der Frage nachgegangen, wie verbreitet homophobe Einstellungen in der Jugend- bzw. Erwachsenenbevölkerung sind. Andererseits werden alters- und länderübergreifend Einflussfaktoren dieser Einstellungen analysiert. Hierfür werden drei Stichproben herangezogen. Die Ergebnisse zeigen, dass je nach Item der genutzten Messinstrumente zwischen 10,3 % und 29,9 % der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Consistent with previous findings, we observed substantial gender differences, with male participants exhibiting higher scores in CU-traits, holding significantly more antigay attitudes, and reporting to engage in antigay bullying more frequently than their female peers (Steffens and Wagner, 2004;Baier and Kamenowski, 2020). An explanation for this effect can be derived from the concept of hegemonic masculinity: those who do not conform to the predominant masculinity construct are devalued, excluded from the group, insulted or attacked (Scheibelhofer, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous findings, we observed substantial gender differences, with male participants exhibiting higher scores in CU-traits, holding significantly more antigay attitudes, and reporting to engage in antigay bullying more frequently than their female peers (Steffens and Wagner, 2004;Baier and Kamenowski, 2020). An explanation for this effect can be derived from the concept of hegemonic masculinity: those who do not conform to the predominant masculinity construct are devalued, excluded from the group, insulted or attacked (Scheibelhofer, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Antigay bullying may represent a particular form of antisocial behavior for its multifaceted socio-ecological origin. For instance, deep faith and religious fundamentalism are strongly related to prejudice based on perceived sexual orientation (Siraj, 2012;Küpper et al, 2017;Baier and Kamenowski, 2020). Thus, one could argue that religion has the potential to function as a surrogate parental figure because it shares many characteristics of "conventional" parental functions, such as providing a secure base (Kirkpatrick and Shaver, 1990;Granqvist and Kirkpatrick, 2008;Granqvist et al, 2010), which complicates the direct relationship between relationship quality and sexual prejudice.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence is mixed with regard to perpetration. While some studies suggest that adolescents with a migration background express more positive attitudes toward immigrants than their peers without a migration background (Losito et al, 2018), others found that they have stronger prejudices toward marginalized social groups such as homosexuals (Baier and Kamenowski, 2020). On the other hand, studies about online hate speech perpetration found no differences between students with and without a migration background (Wachs and Wright, 2018;Wachs et al, 2022a).…”
Section: Differences By Migration Backgroundmentioning
confidence: 99%